DIGITAL LITERACY AND ONLINE TRUST TO AVOID CYBERBULLYING ANONYMITY AMONG TWITTER ROLE PLAYERS COMMUNITY - Hendrayani, Putri Fajar Ayu (Interaksi: Jurnal Ilmu Komunikasi, 2024)
This study aims to present the importance of digital literacy skills and the developed of an online trust to avoid cyberbullying anonymity mechanisms among Twitter role players as a virtual community. This study uses three main theories, namely: “Digital Identities: Creating and Communicating the Online Self”; “Online trust: A Stakeholder Perspective, Concepts, Implications, And Future Directions”; and “Anonymity, Pseudonymity, and Deliberation: Why Not Everything Should Be Connected”. This study uses a quantitative method using a descriptive approach to describe the findings of the results in the field in detail. The cross-table is used as an analytical tool to see whether there is an impact on the variable being tested. In this study, it was found that the results of the analysis on the impact of digital literacy and cyberbullying anonymity using a cross-table showed no impact between the two variables, which means that digital literacy skills have no impact whatsoever on avoiding cyberbullying anonymity among Twitter role players. While the results of the analysis on the impact of online trust and cyberbullying anonymity using a cross-table show that there is an impact in the moderate category between the two variables, which means that the formation of online trust has quite an impact on avoiding cyberbullying anonymity among Twitter role players.